If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + ax = b + 8y(x) Reorder the terms: ax + 4y = b + 8y(x) Multiply y * x ax + 4y = b + 8xy Solving ax + 4y = b + 8xy Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4y' to each side of the equation. ax + 4y + -4y = b + 8xy + -4y Combine like terms: 4y + -4y = 0 ax + 0 = b + 8xy + -4y ax = b + 8xy + -4y Divide each side by 'x'. a = bx-1 + 8y + -4x-1y Simplifying a = bx-1 + 8y + -4x-1y Reorder the terms: a = bx-1 + -4x-1y + 8y
| x^3-x-2= | | -11*-24= | | -9x+9y=27 | | 15n+18=-6n+2 | | 2-2n=3(-n+2) | | 3m+8=3(4+m)-4 | | -48+(-13)= | | 6n+7-2n-14=4n+8 | | h(t)=-t-17 | | 3x^2-16x=64+y | | g(x)=5+0x | | 57+(-104)= | | x^2+x-48=3x | | 3n+6+n-8=2n-2+2n | | 3n+5(n-2)=3n+8(2-n) | | -43+81= | | 7(3-2n)-1=6-7n | | 52+(-7)= | | x^2-4x=-x+70 | | 5(3+x)-(8x+9)=-4 | | a(t)=12-4t | | -38+7= | | 10x+9=2x-7 | | 3x^4(1-x)=0 | | -3.2=-6.8 | | -16+-29= | | x^2+17=-10x+1 | | -2(4-3k)+8k= | | x^2-90=2x-10 | | -8(b-87)=-72 | | 4b+1-b=7 | | 5p+5-6=6p+3-30 |